INTERNALISASI NILAI KULTURAL MUHAMMADIYAH JAWA DALAM PENDIDIKAN DASAR: TINJAUAN PSIKOLOGI PERKEMBANGAN ANAK - Choirunnisa Siregar, Fithri; Wulandari; Ahmad Lahmi; Dasrizal Dahlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The objective of this research is to analyze the internalization of Javanese Muhammadiyah cultural values—a synthesis of progressive Islamic theology and Javanese local wisdom—at the elementary education level through the lens of child developmental psychology. Primary education is a critical phase where children are in the concrete operational stage and undergo rapid moral and social development. This study employs a qualitative descriptive method, utilizing literature reviews and observations across several Muhammadiyah elementary educational institutions in Central Java and Yogyakarta. The findings indicate that the internalization of values, such as andhap ashor (humility), tepa selira (empathy), and a strong work ethic (tajdid), is achieved through three psychological stages: habituation, figurative identification, and significance attribution. Psychologically, the internalization of these cultural values facilitates the development of a positive self-concept and moral autonomy among children. These findings affirm that the Muhammadiyah primary education curriculum serves as a protective pedagogy that transcends mere knowledge transfer, acting instead as an incubation space for a harmonious identity fused from religion and local culture. This research highlights the necessity of strengthening the teacher's role as a social learning model to bridge the gap between traditional values and children's psychosocial development in the digital era.